The Impact of the Collapse of Silicon Valley Bank on the Volatility of Sectoral Stock Indices on the Indonesian Stock Exchange - Fridayana Yudiaatmaja; Trianasari Trianasari (Universitas Pendidikan Ganesha, 2024)
The aim of this research is to determine the impact of the collapse of Silicon Valley Bank (SVB) on the volatility of sectoral stock indices on the Indonesian Stock Exchange. The data collection technique used in this research is documentation. Secondary data were collected from the ten sectors on the Indonesian Stock Exchange, namely agricultural, mining, basic industry, various industries, consumer goods, property, infrastructure, finance, trade and services, and manufacturing, obtained from the Indonesian Stock Exchange website. The data were analyzed using an Android-based t-test application called the Difference Test to compare sectoral stock index volatility before and after the collapse of Silicon Valley Bank. The research results show that almost all sectors were significantly affected by the collapse of SVB, except for companies operating in the industrial sector. The sectors most affected by this incident were companies operating in the technology sector, followed by the raw goods sector. These findings highlight the interconnectedness of global financial events and their ripple effects on different sectors of the Indonesian stock market. This research provides valuable insights for investors and policymakers regarding sectoral vulnerabilities and the importance of monitoring global financial stability.